al Tanzimat al rakhiliyyah fi makkat al mukarramah ba'da dukhul al Malik Abdulaziz al Su'ud (1343 - 1351 H / 1924 - 1932 M) - Muna Binti Qaid al Uthabatah al Qahtaniy (Darah al Malik Abdulaziz, 2006)
sgh.1/sgh.c1